Factors affecting non-performing loans in banking industry: A case of KCB Bank (Tanzania) limited Morogoro and Msimbazi branches - Msigwa, Carlo (Mzumbe University, 2024)
A dissertation submitted in fulfillment of the requirement for the award of the Degree of Masters in Accountancy and Finance (MSc A&F) of Mzumbe University